Manfaat Kegiatan Ekstra Kurikuler Dalam Pengembangan Kompetensi Sosial Siswa SMA - Wafroturrohmah, W.; Sulistiyawati, Eny (Manajemen Pendidikan, 2018)
The specific objective in this study is to obtain the benefits of extra-curricularactivities from students who are active in extra-curricular activities in supportingtheir development, especially students’ social competence which includes theability to cooperate, build social interaction and be able to communicate wellbetween students in the school environment by utilizing resources - sources in theirenvironment to be able to behave appropriately and accurately in all environmentalconditions. This type of research is phenomenological qualitative. Data collectiontechniques used include: observation / observation and interview. The instrumentused consists of: interview guidelines and observation / observation guidelines. Data analysis techniques used are qualitative analysis with steps namely: data reduction, data presentation, discussion and conclusion. Research results: 1) extracurricular activities foster self-confidence, discipline, and courage to speak in public. 2) Extracurricular activities foster independence and maturity that can change their way of thinking if they face problems in their lives. 3) Extra curricular activities become a media for them to discuss and learn together to solve academic problems they face.